2022
DOI: 10.3390/ijerph192215400
|View full text |Cite
|
Sign up to set email alerts
|

Violent Video Game Exposure and Problem Behaviors among Children and Adolescents: The Mediating Role of Deviant Peer Affiliation for Gender and Grade Differences

Abstract: Based on problem behavior theory, a mediation model for gender and grade differences is explored in this study. The study examined gender and grade differences in the effects of violent video games and deviant peer affiliation on problem behaviors among children and adolescents. A total of 2118 children and adolescents from four primary and middle schools in China (M age = 13.08, SD = 2.17) were surveyed using an anonymous questionnaire on basic information, exposure to violent video games, deviant peer affili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Some studies showed a connection between videogame play and decreased academic performance [ 18 , 19 ], while other studies thoroughly documented associations between violent videogames and aggressive behavior in children [ 20 , 21 , 22 , 23 , 24 , 25 ]. However, research suggests that videogames for young people can have both positive and negative effects, depending on the type and extent of use, as well as the presence or absence of protective factors like family support or diminished relations with peers [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed a connection between videogame play and decreased academic performance [ 18 , 19 ], while other studies thoroughly documented associations between violent videogames and aggressive behavior in children [ 20 , 21 , 22 , 23 , 24 , 25 ]. However, research suggests that videogames for young people can have both positive and negative effects, depending on the type and extent of use, as well as the presence or absence of protective factors like family support or diminished relations with peers [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%